Pemberian Edukasi Keluarga Berencana Pada Wanita Usia Subur - Yulia Arifin; Sri Suciana; Ety Aprianti (Institut Nalanda, 2024)
Unmet Need is a married woman of childbearing age who does not want to have more children or wants to space births but does not use contraception. Unmet need for family planning is one of the obstacles to managing family planning programs in Indonesia which requires ongoing handling (Susanti et al., 2023). The percentage of cases of unmet need for family planning based on Central Statistics Data can be said to be high, namely in 2020 it was 5.44%, and it fell in 2021 by 5.03% then rose again in 2022 by 6.09% West Sumatra is one of the regions with a high number of unmet needs in Indonesia. In 2021, the unmet need figure in West Sumatra Province reached 13.6%, consisting of Wanting Delayed Children (IAT) at 6.67% and Don't Want More Children (TIAL) at 6.93%. Meanwhile, the number of unmet needs in Padang City in 2021 is 26.61%. This is still high compared to the DP3AP2KB performance achievement target of 13%. Based on the results of field analysis which was carried out by conducting interviews with two Women of Childbearing Age (WUS) aged 30 and 40 years in the community service area, information was obtained that the two WUS did not use family planning because of the myth that had developed regarding the side effects of using contraceptive methods and they worry if pregnancy occurs. Based on the analysis of the target group's situation, it is deemed important to carry out education-based community service activities (health promotion) in the use of contraceptive methods for WUS in West Padang District. Family planning education activities were carried out at the West Padang District Head Office, Padang City, targeting 100 female couples of childbearing age. The implementation stage of this activity consists of providing information and education to mothers who attended the West Padang District Cheap Market Operation in March 2023. The activities carried out in implementing this program are: Briefing with the Implementing Team, gathering female couples of childbearing age who attend the Murah Market Operation, providing information and education to female couples of childbearing age who are the target of family planning, Providing correct information and education about contraceptives according to complaints from female couples of childbearing age, and Distributing leaflets to every female couple of childbearing age. The activity went smoothly with 70 participants attending. Individual family planning counseling is carried out with female couples of childbearing age, so that the achievement of socialization is 100 percent.